2015
DOI: 10.1002/pc.23586
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dielectric relaxation and ac conductivity behavior of polyvinyl alcohol‐cadmium selenide nanocomposite films

Abstract: We adopt an analytical approach to study the dielectric relaxation and ac conductivity behavior of the polyvinyl alcohol (PVA) -Cadmium Selenide (CdSe) nanocomposite films in the frequency range 100 Hz £ f £ 1 MHz and in the temperature range 298 K £ T £ 420 K. The CdSe nanoparticles are synthesized via a simple wet chemical route and are then impregnated into the polyvinyl alcohol matrix by 0.5 wt%, 1 wt%, and 4 wt%. About 1.7 times increase in effective permittivity (at 100 KHz) for the 4 wt% nanoparticle im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…The PVA and PVP films have very low electrical conduction due to which these are frequently used as a dielectric material for electrical insulation in organoelectronic devices [33][34][35]. The hydroxyl (AOH) and carbonyl (C @ O) functional groups of the PVA and PVP backbone, respectively, exhibit electrostatic interactions with the additives and inorganic nanofillers, and therefore, these hydrophilic polymers are mostly preferred as binders and capping agents in the preparation of advanced composite functional materials [14,[36][37][38][39]. In addition to the pristine polymers, the blend of PVA and PVP realizes its giant applications in the area of electronics, electrical, and biomedical engineering and also in the preparations of various kind of sensors and the energy storing devices [7,18,19,23,[40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The PVA and PVP films have very low electrical conduction due to which these are frequently used as a dielectric material for electrical insulation in organoelectronic devices [33][34][35]. The hydroxyl (AOH) and carbonyl (C @ O) functional groups of the PVA and PVP backbone, respectively, exhibit electrostatic interactions with the additives and inorganic nanofillers, and therefore, these hydrophilic polymers are mostly preferred as binders and capping agents in the preparation of advanced composite functional materials [14,[36][37][38][39]. In addition to the pristine polymers, the blend of PVA and PVP realizes its giant applications in the area of electronics, electrical, and biomedical engineering and also in the preparations of various kind of sensors and the energy storing devices [7,18,19,23,[40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…So, variation of s with temperature for each sample was studied and found that in each case, s decreased with increase in temperature ( Fig. 10) decisively suggesting that AC conduction mechanism in all the samples can be clearly understood through CBH model [38,75]. According to this model, charge transport is suggested to be due to thermal activation over the barrier between two sites, each having a coulombic potential well associated with it.…”
Section: Ac Conductivity Analysismentioning
confidence: 93%
“…Effective permittivity ( ′ ), decreases with increase of frequency ( Fig. 5b) whereas at higher frequencies dipoles can no longer follow the field, as a result of which, effective permittivity decreases [11]. At higher frequencies, dipoles slowly fall off the electric field [30] which leads to decrease in dielectric amount [38,39].…”
Section: Dielectric Study Of the Qdsmentioning
confidence: 99%
“…Many of these applications are greatly benefited by existence of quantum dots with their extensive and unique properties. For instance, dielectric characteristics of QDs can enhance the electro-optical properties of nano-composites like, liquid crystals [9,10], polymer matrix [11][12][13], graphene and hybrid graphene [14][15][16]. Polymeric nano-composites consisting of conductive nanoparticles are mostly used in electronic devices offering wide and low-budget fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation